The Role of Auditor Independence, Professionalism, Skepticism, and Organizational Culture on Auditor Performance - Achmad Fauzi; Jurica Lucyanda; Fadil Permana; Tifani Margaretha; Mila Novita (Universitas Negeri Semarang, 2024)
Purposes: This study aims to examine the role of internal and external factors in auditor performance. This study uses auditor independence, professionalism, and skepticism as internal factors and organizational culture as external factors. Methods: Drawing on the attribution theory to develop and test the hypotheses, this study conducts a survey method using an electronic questionnaire to collect data. The respondents are auditors working in the Big Four public accounting firms. Data are analyzed using multiple linear regression models. Findings: The results show that auditor independence, professionalism, skepticism, and organizational culture positively influence auditor performance. These findings confirmed the attribution theory that dispositional attribution and situational attribution play a key role in individual attributions, namely auditor performance. Novelty: This study contributes to behavioral management accounting research, specifically the performance of auditors. Limited research still uses organizational culture as an external factor that may affect auditor performance. The attribution theory complements previous studies investigating the determinants influencing auditor performance, from internal (dispositional attributions) to external (situational attributions) factors.